A questão da escravatura em Luís de Molina - Rebalde, João (2021)
In De iustitia et iure Luis de Molina distinguishes between different meanings of servitude and considers slavery to be licit if it is practised within the framework of certain conditions. This article studies Molina's position, showing that the precise definition of the conditions under which slavery is licit allows him to limit the legal scope of this practice, to denounce the injustices of the slave trade, to claim the regulation of political and ecclesiastical power, and to frame a set of slave rights.